Medical terminology circulation and interactional organisation in interpreter-mediated medical encounters - Pittarello, Sara (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Two medical encounters taking place in a Northern Italian hospital are analysed in this paper from a qualitative point of view, based on the author’s previous research. The aim is to reveal the strategies adopted by medical interpreters, in these two specific cases, to translate medical terminology and promote/exclude interlocutors’ active participation. This latter aspect is influenced by the way the interaction is socially and linguistically organised and, in particular, by how interlocutors’ utterances are translated. The prevalence of dyadic or triadic sequences and especially the shifts between such communication exchanges are pivotal in fostering or hindering interlocutors’ participation. Furthermore, medical interactions, as a form of institutional talk, enshrine specific expectations, which are mainly of a cognitive nature but may also be affective, as in the two encounters observed. By conveying such expectations and expressions of personal interest, interpreters have proved to contribute to the fair distribution of active participation among primary interlocutors. Hospital ethical approval and subjects’ written informed consent have been obtained.